Bismuth Oxychloride as an Efficient Heterogeneous Catalyst for Aldol Condensation Reaction between Aldehydes and Ketones - Nguyen Thi Kim Oanh; Nguyen Vinh Huu; Linh Xuan Nong (Bulletin of Chemical Reaction Engineering & Catalysis, 2023)
The aldol reaction is a cornerstone of modern synthetic organic chemistry in which the β-hydroxyketone was formed by the reaction of an enol or an enolate and a carbonyl compound. Benzalacetone is one of the fundamental building blocks of benzalacetone synthase structure that play an important role for construction of a variety of medicinally crucial phenylbutanoids, such as anti-inflammatory glucoside lindleyin in rhubarb and gingerol. The non-transition metal material attracted much attention from research groups on the world, such a potential catalyst as BiOCl for organic reaction due to its remarkably chemical and physical properties as relative stability, resistance of air and moisture, low toxicity. The BiOCl material was synthesized by the solvothermal method. The structure features of material were defined by modern analytic methods such as X-ray diffraction (XRD), Fourier Transform infrared spectroscopy (FT-IR), Scaning Electron Microscope (SEM), and Nitrogen Adsorption-Desorption Isotherms. The BiOCl material was successfully utilized as a catalyst for the aldol condensation reaction of benzaldehyde and acetone. The reaction was performed in the mild condition with the presence of 10 mol% catalyst and 2 equivalent of Cs2CO3 as base without by-product in very short reaction times and good yields. The benzalacetone product obtained around 85% yield at 120 °C for 24 h. The BiOCl material after reaction was recovered and reused many times without significant reducing of catalytic activity. Copyright © 2023 by Authors, Published by BCREC Group. This is an open access article under the CC BY-SA License (https://creativecommons.org/licenses/by-sa/4.0).